PENGARUH PENAMBAHAN EKSTRAK UBI JALAR PUTIH TERHADAP KARAKTERISTIK SIRUP NANAS - -, Cengristitama; Rochma, Siti; Sari, Myra Wardati (UPPM Politeknik TEDC Bandung, 2023)
Pineapple (Ananas comosus L. Merr) is a fruit that is always available throughout the year and makes this fruit a superior agricultural commodity in Indonesia. But, pineapples are easily damaged and decay quickly. An alternative to inhibit the damage process by processing it into pineapple syrup. This study’s aim was to determine the effect of adding white sweet potato extract to the characteristics of pineapple syrup. This research was conducted using an experimental method consisting of 1 factor, namely without variation of white sweet potato as a control (0%), 10%, 20%, 30% and 40%, so that it got 5 treatments with 2 repetitions. The research started by making white sweet potato extract, making pineapple syrup, testing vitamin C, total sugar content, viscosity and organoleptic testing. The research was conducted in accordance with SNI 3544-2013 about syrup. The results showed that the organoleptic test of pineapple syrup obtained an assessment of the taste parameters on NU1 of 3,2 (like) and on the aroma is treatment NU3 of 3,0 (like), and color on NU2 of 3,10 (like). The best results were obtained from pineapple syrup with treatment at a concentration of 10% white sweet potato extract with the observed parameters: vitamin C of 0,35%, viscosity of 31,53 cP and total sugar content of 6,4%.